The Late Bronze and Early Iron Ages of Southern Canaan - Maeir, Aren M.; McKinny, Chris; Shai, Itzhaq (Archaeology of the Biblical Worlds ;, 2019)
The Late Bronze Age in the Levant is a period of much interest to archaeologists, historians and biblical scholars. This is a period with intense international relations, rich in ancient sources, which provide historical data for the period, and is a crucial formative period for the peoples and cultures who play central roles in the Hebrew Bible. Recent archaeological research in Israel and surrounding countries has provided new, exciting, and in some cases, groundbreaking finds, interpretations and understanding of this period.The fourteen papers in this volume represent the proceedings of a conference held at Bar-Ilan University in 2014 (with the additional of several invited papers not presented at the conference), which provide both overviews of Late Bronze Age finds from several important sites in Israel and surrounding countries, as well as several synthetic studies on the various issues relating to the period. These papers, by and large, represent a broad view of cuttting edge research in the archaeology of the ancient Levant in general, and on the Late Bronze Age specifically.